Cambio. - Gallo, Rubén; Garcia de Oteyza, Juan; Monges, Lourdes; Ortega, Luis Felipe; Schachter, Kenny; Turner, Grady T.; Volk, Gregory; Galeria OMR, Mexico; La Torre de los Vientos, Mexico; Museo Universitario del Chopo, Mexico; Sandra Gering Gallery, New York; Temporary Gallery Space, New York (New York : Mexican Cultural Instiute, 1997)
Abaroa, Eduardo ; Aguirre, Carlos ; Albenda, Ricci ; Artemio ; Botey, Mariana ; Brunet, Fernanda ; Cass, Brendan ; Chambers, Robert ; Cuevas, Minerva ; Gillmore, Graham ; Gout, Leopoldo ; Guzman, Daniel ; Harrison, Rachel ; Horowitz, Jonathan ; Itagaki, Yoshio ; Jiménez, Cisco ; Keightley, Tricia ; Lekay, John ; Malka, Ilona ; Martinez, Alfredo ; Medina, Diego ; Minelli, Michael ; Okun, Yoshua ; Orlaineta, Edgar ; Ortega, Luis Felipe ; Razo, Vincente ; Roach, John ; Root, Ruth ; Rossell, Daniela ; Ruyter, Lisa ; Schachter, Kenny ; Seeman, Bonnie ; Seward, Lawrence ; Sierra, Santiago ; Taylor, Rodney ; Ventura, Miguel
biog., ind. tent., gr. tent. bibliog., prijzen per kunstenaar
Cambio, Temporary Gallery Space, New York, November / December 1997 ; Sandra Gering Gallery, January 1998 ; Museo Universitario del Chopo, Mexico, August / September 1998 ; La Torre de los Vientos, Mexico City, August 1998 ; Galeria OMR, Mexico, Spring 1999
Engels & Spaans
boek
Keywords: Mexico; U.S.A.